2013
DOI: 10.1177/0218492313485070
|View full text |Cite
|
Sign up to set email alerts
|

Double-valve surgery in Shprintzen-Goldberg syndrome

Abstract: We describe the challenging case of a 28-year-old Jehovah's Witness patient who presented with symptomatic mitral and tricuspid valve disease and Shprintzen-Goldberg syndrome. This is the first reported double-valve surgery in such a patient who, apart from chest deformity, had a small body size, severe lung disease, difficult airway and vascular access, and to add to the complexity, refused blood and blood product use. The patient underwent a successful mitral valve replacement and tricuspid valve repair thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In addition to a meticulous clinical examination, a high degree of suspicion is critical in corroborating the clinical and imaging findings to that of a classical case described by Greally et al 27 Pauliks et al 25 reported the first case of complex congenital heart disease in a neonate with Shprintzen-Goldberg syndrome. Likewise, Elmistekawy et al 28 descibed the first double valve surgery in a patient with Shprintzen-Goldberg syndrome that presented with increasingly severe mitral regurgitation due to bileaflet prolapse, and tricuspid valve regurgitation. Pavone et al 29 reported their findings of a boy aged 16 years, affected by this syndrome that was followed up for 12 years to evaluate the clinical course and underlined the presence of the teeth malformations amongst the various clinical signs of Shprintzen-Goldberg syndrome; fortunately such findings were absent in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a meticulous clinical examination, a high degree of suspicion is critical in corroborating the clinical and imaging findings to that of a classical case described by Greally et al 27 Pauliks et al 25 reported the first case of complex congenital heart disease in a neonate with Shprintzen-Goldberg syndrome. Likewise, Elmistekawy et al 28 descibed the first double valve surgery in a patient with Shprintzen-Goldberg syndrome that presented with increasingly severe mitral regurgitation due to bileaflet prolapse, and tricuspid valve regurgitation. Pavone et al 29 reported their findings of a boy aged 16 years, affected by this syndrome that was followed up for 12 years to evaluate the clinical course and underlined the presence of the teeth malformations amongst the various clinical signs of Shprintzen-Goldberg syndrome; fortunately such findings were absent in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a meticulous clinical examination, a high degree of suspicion is critical in corroborating the clinical and imaging findings to that of a classical case described by Greally 27 Pauliks et al 25 reported the first case of complex congenital heart disease in a neonate with Shprintzen-Goldberg syndrome. Likewise, Elmistekawy et al 28 descibed the first double valve surgery in a patient with Shprintzen-Goldberg syndrome that presented with increasingly severe mitral regurgitation due to bileaflet prolapse, and tricuspid valve regurgitation. Pavone et al 29 reported their findings of a boy aged 16 years, affected by this syndrome that was followed up for 12 years to evaluate the clinical course and underlined the presence of the teeth malformations amongst the various clinical signs of Shprintzen-Goldberg syndrome; fortunately such findings were absent in our patient.…”
Section: Discussionmentioning
confidence: 99%